Diproline-induced resistance to parasitic nematodes in the same and subsequent rice generations: Roles of iron, nitric oxide and ethylene - De Kesel, Jonas; Bonneure, Eli; Frei, Michael; De Meyer, Tim; Mangelinckx, Sven; Kyndt, Tina (Frontiers in Plant Science, 2023)
Induced resistance (IR) is a plant phenotype characterized by lower susceptibility to biotic challenges upon elicitation by so-called IR stimuli. Earlier, we identified diproline (cyclo(L-Pro-L-Pro)) as IR stimulus that protects rice (Oryza sativa) against the root-knot nematode Meloidogyne graminicola (Mg). In the current study, detailed transcriptome analyses at different time points, and under uninfected and nematode-infected conditions revealed that this rice IR phenotype is correlated with induction of genes related to iron (Fe), ethylene (ET) and reactive oxygen species (ROS)/reactive nitrogen species (RNS) metabolism. An infection experiment under Fe limiting conditions confirmed that diproline-IR is only effective under optimal Fe supply. Although total root Fe levels were not affected in diproline-treated plants, phytosiderophore secretion was found to be induced by this treatment. Experiments on mutant and transgenic rice lines impaired in ET or ROS/RNS metabolism confirmed that these metabolites are involved in diproline-IR. Finally, we provide evidence for transgenerational inheritance of diproline-IR (diproline-TIR), as two successive generations of diproline-treated ancestors exhibited an IR phenotype while themselves never being exposed to diproline. Transcriptome analyses on the offspring plants revealed extensive overlap between the pathways underpinning diproline-IR and diproline-TIR. Although diproline induces significant systemic changes in global DNA methylation levels early after treatment, such changes in DNA methylation were not detected in the descendants of these plants. To our knowledge, this is the first report of TIR in rice and the first transcriptional assessment of TIR in monocots.